Pengaruh customer relationship marketing dan customer bonding terhadap loyalitas pelanggan dengan kepuasan pelanggan sebagai variabel intervening pada grapari telkomsel makassar - Sapanang, A.Baso Aditya; Maupa, Haris; Jusni (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of customer relationship marketing and customer bonding, on customer loyalty with customer satisfaction as an intervening variable at Grapari Telkomsel Makassar. This research uses a quantitative approach, the population in this study are corporate customers from Grapari Telkomsel Makassar (corporate customers) totaling 150 customers, then the sampling using the Slovin formula so that the respondents totaled 60 respondents. Data was collected using a survey method on 60 respondents who are corporate customers of Grapari Telkomsel Makassar. The results showed that the customer relationship marketing variable consisting of communication, commitment and conflict handling had a direct and significant positive effect on customer loyalty, as evidenced by the statistical output value which stated the value of sig < 0.05 but by testing using the intervening variable, namely through customer satisfaction, customer relationship marketing does not have an indirect influence on customer loyalty, as evidenced by the value of direct influence > the value of indirect influence, then customer bonding variables consisting of awareness bonding, financial bonding and advocacy bonding have a significant positive direct effect on customer loyalty as evidenced by the value the output statistic which states the value of sig < 0.05, and also has an indirect effect on customer loyalty as evidenced by the magnitude of the indirect effect > direct influence, and the last to customer satisfaction has a direct and significant positive effect on customer loyalty grapari telkomsel Makassar is evidenced by the results of the regression which states the level of significance value <0.05.